Revaluation of Turkey's energy policy connected with energy sources - Şeker, Şahin Serhat; Kaynaş, Tayfun; Ayhan, Damla (Int Scientific Conference SGEM, 14, Kilment Ohridsky BLVD, Sofia, 1797, Bulgaria, 2010)
Energy demand and consumption is one of the key factors of a country's level of development. They are not only related with economic development but also the dimension of security and environment should be taken into account. Hence, sustainability and resource diversity have overriding importance for the countries. Turkey has a considerably high level of renewable energy resources that can be a part of the total energy network in the country The optimum use of Turkey's non-renewable and renewable resources should receive attention in technological and economical development of the country. The study aims to determine new targets related to the potential of renewable and non-renewable energy sources in Turkey. In this direction a new classification which is compatible with economy, technology and environment has been done to determine a new energy policy. According to this classification, energy investment oriented items have been determined. As a result, the necessity of new investments of renewable energy sources in Turkey has been emphasized.
Keywords: Energy policy; renewable energy sources; unrenewable energy sources; energy technology